Role of House Fly, Musca domestica (Diptera: Muscidae) as a Mechanical Vector of pathogenic Bacteria in Thi Qar Province - Lhoak, Hussein Anad; Al-Awadi, Alaa Hussein (Medicra (Journal of Medical Laboratory Science/Technology), 2024)
The common house fly, known as Musca domestica, has been acknowledged to carry and spread numerous contagious illnesses. The purpose of this investigation is to uncover the extent of the house fly's involvement as a carrier of harmful bacteria that can lead to diseases in both humans and animals. To accomplish this goal, a collection process was conducted using manual traps from March 2023 until July 2023. I collected house flies from various locations in Thi Qar province. A total of 370 samples were gathered, out of which 270 flies were utilized to isolate bacteria from both the outer and inner surfaces. To identify the house flies, I sent 100 of them to the Natural History Museum at the University of Basra. The current study recorded among 270 flies 104 (38.52%) have not bacteria, while 166 (61.48%) have bacteria. The results were recorded the highest isolated bacteria from outer surface 94 (34.81%) and 72 (26.67%) from inner surface, in contrast the lowest negative bacteria were from outer surface 41 (15.19%), and 63 (23.33%) inner surfaces. The study recorded the highest number of isolated bacteria were from Arido 23 (8.52%), followed in both Al-Sharqiyah and Altathhia 22 (8.15%), followed by Shuhadda, Ur and Summer 21 (7.78%), while the lowest isolated bacteria were in Shmoukh 4 (1.48%), followed in both Aledara almahaleia 14 (5.19%). The current study recorded the most isolated bacteria was P. Vulgaris 21 (20.19%), followed by P. mirabilis 18 (17.31%), followed by S. aureus 11 (10.58%), in contrast the lowest isolated bacteria were P. stuartii 1 (0.96%), followed by both S. paucimobilis and S. maltophilia 2 (1.92%).